QUESTIONS MODERN EPILEPTOLOGY - G. N. Avakyan (Эпилепсия и пароксизмальные состояния)
Recent epidemiological studies in 16 regions of the Russian Federation showed that seizures in patients with epilepsy missing only 14.93% of patients. Less than 5% of patients receiving "new" anti-epileptic drugs (AEDs). In many cases, drugs are administered in doses lower than therapeutic. Hence the need to optimize the treatment, research new technologies and AEDs to treat drug-resistant epilepsy.